(untitled) (Asian Journal of Medical and Biological Research, 2020)
Performance evaluation of existing dairying is important to design relevant dairy development strategies and implement context specific interventions for future development of the dairy enterprise. The present study was carried out to evaluate the clinical trends (reproductive performance and disorders) of dairy cows of Rajshahi district, Bangladesh. A total of 500 cows randomly selected and data were collected directly from the dairy farms owners from 6 upazilas and 4 metro thanas of Rajshahi district by using questionnaires and diagnosis of reproductive disorders (RD) was made on the basis of history, clinical signs and response to treatment. The average reproductive performance (RP) were recorded as age at puberty 26.42±0.22 m, age at first calving 35.48±0.22 m, post-partum heat period 121.85±3.48 days, service per conception 1.93±0.04, days open 136.80±3.57 days and calving interval 401.04±3.94 days. The better RP was found at metro thanas compared to upazilas, though no significant difference was found except on service per conception (p<0.05). The overall prevalence of RD was 78.6% in Rajshahi district. Among the reproductive and productive disorders, anoestrus 24.6% was the highest prevalent disorders followed by abortion 13.4%, repeat breeding 11.4%, retained placenta 10.2%, dystocia 5.4%, mastitis 4.4%, vaginal prolapse 2.4%, pyometra 1.8%, metritis 1.6%, uterine prolapse 1.4%, milk fever 1.2% and still birth 0.8%. The highest occurrence of RD was recorded in Tanore upazila (92%) and the lowest in Poba upazila (62%). In comparison between the upazila and metro thanas the minimum occurrence of RD was recorded in metro thanas (31%) than upazilas (47.6%). Asian J. Med. Biol. Res. June 2020, 6(2): 340-350